2005
DOI: 10.1200/jco.2005.05.188
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Biopsy After Neoadjuvant Chemotherapy in Breast Cancer: Results From National Surgical Adjuvant Breast and Bowel Project Protocol B-27

Abstract: These results are comparable to those obtained from multicenter studies evaluating SNB before systemic therapy and suggest that the sentinel node concept is applicable following neoadjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
263
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(275 citation statements)
references
References 32 publications
9
263
1
2
Order By: Relevance
“…PC was initially considered a contraindication to the sentinel node procedure. Subsequent data from the NSABP B27 study reported by Mamounas et al [30] as well as data from a meta-analysis [31] demonstrated that the sentinel node procedure is as accurate after PC as it is without prior chemotherapy. These data have resulted in national guidelines stating the acceptability of the sentinel node procedure after PC [32].…”
Section: Discussionmentioning
confidence: 99%
“…PC was initially considered a contraindication to the sentinel node procedure. Subsequent data from the NSABP B27 study reported by Mamounas et al [30] as well as data from a meta-analysis [31] demonstrated that the sentinel node procedure is as accurate after PC as it is without prior chemotherapy. These data have resulted in national guidelines stating the acceptability of the sentinel node procedure after PC [32].…”
Section: Discussionmentioning
confidence: 99%
“…One of the significant benefits of NAC is downstaging of the tumor in the breast and in the axillary nodes and thereby enabling breast conservation and possibly avoiding AD [22][23]. With certain tumor subtypes as triple negative and Her2 (+) breast cancer, axillary pathological complete response (pCR) rates of 30% have been reported when using anthracycline-based regimens reaching 40% with the use of taxane-based regimens [24][25]. In Her2 (+) patients, the addition of trastuzumab increases the pCR rates in the axilla to 70% [26].…”
Section: Reviewmentioning
confidence: 99%
“…Several methods have been proposed for estimating recurrence in those with less than a pCR based upon the posttreatment stage [95] or an algorithm based upon posttreatment pathologic features [96,97]. For patients who have clinically negative nodes after PST, sentinel lymph node biopsy appears to have similar accuracy as when done preoperatively [98]. Preliminary experience with preoperative endocrine therapy in older individuals with HR-positive disease has also been advocated by some experts, because changes in proliferation index after a short course of therapy correlate with recurrence [99], although this approach has generally been restricted to patients enrolled on CTs [100].…”
Section: Preoperative Neoadjuvant Systemic Therapymentioning
confidence: 99%